The Heterooligomerization of Human Small Heat Shock Proteins Is Controlled by Conserved Motif Located in the N-Terminal Domain - Shatov, Vladislav M. (Int J Mol Sci, 2020)
Ubiquitously expressed human small heat shock proteins (sHsps) HspB1, HspB5, HspB6 and HspB8 contain a conserved motif (S/G)RLFD in their N-terminal domain. For each of them, we prepared mutants with a replacement of the conserved R by A (R/A mutants) and a complete deletion of the pentapeptide (Δ mutants) and analyzed their heterooligomerization with other wild-type (WT) human sHsps. We found that WT HspB1 and HspB5 formed heterooligomers with HspB6 only upon heating. In contrast, both HspB1 mutants interacted with WT HspB6 even at low temperature. HspB1/HspB6 heterooligomers revealed a broad size distribution with equimolar ratio suggestive of heterodimers as building blocks, while HspB5/HspB6 heterooligomers had an approximate 2:1 ratio. In contrast, R/A or Δ mutants of HspB6, when mixed with either HspB1 or HspB5, resulted in heterooligomers with a highly variable molar ratio and a decreased HspB6 incorporation. No heterooligomerization of HspB8 or its mutants with either HspB1 or HspB5 could be detected. Finally, R/A or Δ mutations had no effect on heterooligomerization of HspB1 and HspB5 as analyzed by ion exchange chromatography. We conclude that the conserved N-terminal motif plays an important role in heterooligomer formation, as especially pronounced in HspB6 lacking the C-terminal IXI motif.